Hydrostatic Pressure Modulates Intervertebral Disc Cell Survival and Extracellular Matrix Homeostasis via Regulating Hippo-YAP/TAZ Pathway - Yiyang Wang; Baoshuai Bai; Yanzhu Hu; Haoming Wang; Ningyuan Liu; Yibo Li; Pei Li; Guangdong Zhou; Qiang Zhou (Stem Cells International)
Established studies proved that hydrostatic pressure had multiple effects on the biological behavior of the intervertebral disc (IVD). However, the conclusions of the previous studies were inconsistent, due to the difference in hydrostatic loading devices and observing methods used in these studies. The current study is aimed at investigating the role of dynamic hydrostatic pressure in regulating biological behavior of the notochordal nucleus pulposus (NP) and fibrocartilaginous inner annulus fibrosus (AF) and its possible mechanism using our novel self-developed hydrostatic pressure bioreactor. The differences in the biological behavior of the rabbit IVD tissues under different degree of hydrostatic pressure were evaluated via histological analysis. Results revealed that low-loading dynamic hydrostatic pressure was beneficial for cell survival and extracellular matrix (ECM) homeostasis in notochordal NP and fibrocartilaginous inner AF via upregulating N-cadherin (N-CDH) and integrin β1. In comparison, high-magnitude dynamic hydrostatic pressure aggravated the breakdown of ECM homeostasis in NP and inner AF via enhancing the Hippo-YAP/TAZ pathway-mediated cell apoptosis. Moreover, inner AF exhibited greater tolerance to physiological medium-loading degree of hydrostatic pressure than notochordal NP. The potential mechanism was related to the differential expression of mechanosensing factors in notochordal NP and fibrocartilaginous inner AF, which affects the fate of the cells under hydrostatic pressure. Our findings may provide a better understanding of the regulatory role of hydrostatic pressure on the cellular fate commitment and matrix metabolism of the IVD and more substantial evidence for using hydrostatic pressure bioreactor in exploring the IVD degeneration mechanism as well as regeneration strategies.